A STUDY ON FINANCIAL PERFORMANCE OF ICICI BANK - BANANA, Dr. KRISHNA; CHEPURI, V.RAMA KRISHNA RAO; POLISETTY, V. VERANJANEYA KUMAR (IJRDO - Journal of Business Management, 2017)
The growth of any economy is based on the financial system prevailed in it. The major components of the financial system are financial assets, financial intermediary/institution, financial markets, financial instruments and financial services. A financial intermediary plays a dominant role in the system. Financial intermediaries include banking system, insurance, development banks and other financial organisations. Performance evaluation of the banking sector is an effective measure and indicator to check the reliability of economic activities of an economy. The present study focuses on the individual evaluation of ICICI Bank. The study adopts an analytical and descriptive research design. The data for a period of 10 years i.e., 2007-08 to 2016-17 have been collected from the annual reports of the bank. Seven ratios are selected for the study and made an analysis of selected ratios using growth rate, average, cumulative annual growth rate and other statistical techniques. The study revealed that the bank performing progressively till 2015, later identified a decline in the performance due to Non Performing Assets.